2015
DOI: 10.3390/ijerph120707235
|View full text |Cite
|
Sign up to set email alerts
|

The Prefrontal Cortex Activity and Psychological Effects of Viewing Forest Landscapes in Autumn Season

Abstract: Recently reported research indicate that forest environments have physiological and psychological relaxing effects compared to urban environments. However, some researchers claim that the stress of the subjects from being watched by others during measurements can affect the measurement result in urban experiments conducted in the center of a street. The present study was conducted to determine whether forest environments have physiological and psychological relaxing effects, using comparison of viewing a fores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 21 publications
8
63
1
3
Order By: Relevance
“…Furthermore, after exposure to the forest environment, SVS scores were higher than after exposure to the urban environment. Consistent with previous studies [2,5,10,11,14,17,33,34], this study confirmed that short periods of forest recreation in a snow-covered forest (in this case: 15 minutes of relaxation in this environment) have a significant effect on mood states of participants. The negative indices of mood states, including tension-anxiety, anger-hostility, depression-dejection, confusion, and fatigue, decreased after exposure to the forest environment.…”
Section: Svssupporting
confidence: 91%
“…Furthermore, after exposure to the forest environment, SVS scores were higher than after exposure to the urban environment. Consistent with previous studies [2,5,10,11,14,17,33,34], this study confirmed that short periods of forest recreation in a snow-covered forest (in this case: 15 minutes of relaxation in this environment) have a significant effect on mood states of participants. The negative indices of mood states, including tension-anxiety, anger-hostility, depression-dejection, confusion, and fatigue, decreased after exposure to the forest environment.…”
Section: Svssupporting
confidence: 91%
“…This result was different from some existing research conclusions. Some studies suggested that for stress reduction, more nature was better [14][15][16][17]41,42]. However, some studies have not indicated that the more natural the environment, the better the effect of relieving stress.…”
Section: The More Natural Not Necessarily the Better: The Decompressmentioning
confidence: 99%
“…Moreover, compared with a city setting, a forest therapy program led to a significant increase in parasympathetic nerve activity [19] and lower sympathetic nerve activity [17]. Additionally, some research has shown that compared with the urban environment, forest therapy was capable of enhancing positive mood states and reducing negative mood states as specific psychological responses [20][21][22][23]. In addition, forest therapy trips resulted in an increase in natural killer (NK) cell activity, which was mediated by increases in the number of NK cells and the levels of intracellular granulysin, perforin, and granzymes A/B in peripheral blood lymphocytes (PBLs) [24][25][26].…”
Section: Introductionmentioning
confidence: 99%